Frequency of Depressive Symptoms in Women with Polycystic Ovary Syndrome and Obesity versus Women with Polycystic Ovary Syndrome without Obesity : Depressive Symptoms in PCOS and Obesity - Faryal, Sheeba; Nighat, Ayesha; Ahmed, Adnan; Bashir, Saba; Liaquat, Farah; Shah, Hanozia (Pakistan Journal of Health Sciences, 2024)
Polycystic Ovary Syndrome (PCOS) is a complicated hormonal condition that impacts women globally. Its association with obesity and its potential impact on mental health, specifically depressive symptoms, has gained increasing attention. This study aimed to determine the relationship between depressive symptoms and PCOS in women, with a focus on the influence of obesity. Objective: To compare the frequency of depressive symptoms among women who have PCOS, categorized based on whether they are obese or not. Methods: A cross sectional descriptive study was conducted on electronic medical records of 194 women with PCOS from a tertiary care hospital. Data included demographic information, clinical characteristics of PCOS, and depressive symptom scores measured using the Center for Epidemiologic Studies-Depression (CES-D) scale. The study was conducted from Apr 2021 to Oct 2021 for a period of 6 months. Results: Women with PCOS and obesity exhibited significantly higher mean CES-D scores and a higher prevalence of clinically significant depressive symptoms (CES-D ≥ 16) compared to those without obesity. Hyperandrogenism, oligomenorrhea, and hirsutism were more prevalent in women with PCOS and obesity. Conclusions: The study found out that women with PCOS and obesity appear to be at a higher risk of experiencing clinically significant depressive symptoms. Healthcare providers should consider the mental health needs of this population, emphasizing a multidisciplinary approach to care.